Pengembangan LKPD Berbasis STEAM untuk Melatih Kreativitas Siswa dalam Pembuatan Karya Seni Rupa di Kelas III Madrasah Ibtidaiyah - Suherman (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2026)
This study addresses the low student creativity and scarcity of innovative STEAM-based worksheets in Islamic Elementary Schools (Madrasah Ibtidaiyah). It aims to develop and test STEAM-based worksheets for third-grade visual arts. The research fills the gap between theory and practice by providing a contextual instructional product. Using the R&D method with the 4D model, the study involved expert validation, practicality tests with teachers and students, and effectiveness testing with a pretest-posttest design. Key results show the worksheets were highly valid (average score 3.72), highly practical, and effective in significantly improving creativity (p<0.05) with a large effect size (0.82). The N-Gain score of 0.68 (moderate category) demonstrates meaningful improvement, with the highest growth in originality.